Sprache – Macht – Schule: Dekoloniale Perspektiven auf die Mehrsprachigkeit - Zingg, Irène (Swiss Journal of Sociocultural Anthropology, 2020)
This article reflects on how language can be a hegemonic practice, as illustrated by the term linguicism. This linguistic discrimination is used to legitimate an unequal division of power and needs to be tackled through decolonial approaches. Switzerland has an offcial tradition of multilingualism, yet people in Switzerland experience discrimination depending on the languages they speak. Pupils in Switzerland are increasingly multilingual but, given their transnational family backgrounds, not always in an offcial Swiss language. Pupils and teachers perceive and value languages differently, often at a subconscious level. Where pupils speak a prestigious language, their language skills are more highly valued. If multilingualism is coupled with a language of migration, a negative connotation occurs and students experience linguicism.